The Sanctioning Power of the Administration in the Public Procurement Scope: The Cases of Peru and Colombia - Quintero Múnera, Andrés (2015)
Initially the exercise of sanctioning powers is contextualized in the field of government procurement in Colombia, regulatory and jurisprudential development of this power and the procedure envisaged by the legislature for the imposition of sanctions is exposed when a violation or breach of it becomes apparent the contractor’s obligations, specifying the scope and gaps that the process involves. Then the consecration of the sanctioning power of the administration is presented in the Peruvian law, marking the differences with the model adopted by the Colombian law, to conclude with some perspectives on the subject.